2018
DOI: 10.3389/fmicb.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity and Evolution of the Fish Pathogen Flavobacterium psychrophilum

Abstract: Flavobacterium psychrophilum, the etiological agent of rainbow trout fry syndrome and bacterial cold-water disease in salmonid fish, is currently one of the main bacterial pathogens hampering the productivity of salmonid farming worldwide. In this study, the genomic diversity of the F. psychrophilum species is analyzed using a set of 41 genomes, including 30 newly sequenced isolates. These were selected on the basis of available MLST data with the two-fold objective of maximizing the coverage of the species di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 93 publications
5
56
1
Order By: Relevance
“…Within North America, CC-ST10 was the most widespread among currently recognized CCs, being detected in 16 of the 20 states in the Northwest, West, Southwest, Midwest, Southeast, and Northeast regions of the United States that were examined in this study. This finding is consistent with other studies that have suggested that ST10, the predicted CC founder strain (12), along with other CC-ST10 STs, have been disseminated around the world as a result of the international salmonid egg trade, where they are also now widespread (13,17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Within North America, CC-ST10 was the most widespread among currently recognized CCs, being detected in 16 of the 20 states in the Northwest, West, Southwest, Midwest, Southeast, and Northeast regions of the United States that were examined in this study. This finding is consistent with other studies that have suggested that ST10, the predicted CC founder strain (12), along with other CC-ST10 STs, have been disseminated around the world as a result of the international salmonid egg trade, where they are also now widespread (13,17).…”
Section: Discussionsupporting
confidence: 92%
“…Combining data from this study with those of Nicolas et al (7) and Van Vliet et al (13) revealed that the mean gene diversity of MLST-typed F. psychrophilum in North America is higher than in all other studied continents (i.e., 0.68 in North America versus 0.48 to 0.66 elsewhere). In this context, a recent study provided evidence that the main lineage of F. psychrophilum causing disease in rainbow trout (i.e., CC-ST10) may have originated in North America, from where at least one successful genotype (e.g., ST10) was distributed to other regions of the world through the international trade of fish (17). If this F. psychrophilum lineage did indeed originate in North America, it would have had more time to diversify in this region, perhaps resulting in the high apparent genetic diversity discovered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of low variation and higher variation genes likely contribute to the topology inconsistencies observed between markers. Due to the observation of variable topologies following phylogenetic analyses of different markers in the present and previous studies, future research should critically analyze whole genome sequences and construct genome based phylogenies to gain a better understanding of how these genetic groups were established as was recently published with F. psychrophilum ( Duchaud et al, 2018 ).…”
Section: Resultsmentioning
confidence: 84%
“…In fact, using less water surface, Chile competes to Norway in salmon production [12]. As consequence, Chilean aquaculture has faced several sanitary problems, related with outbreaks of viruses such as infectious pancreatic necrosis virus (IPNV) [13] and infectious salmon anemia virus (ISAV) [14]; bacterial pathogens such as Piscirickettsia salmonis [15], Flavobacterium psychrophilum [16], and Renibacterium salmoninarum [17]; and parasites such as Caligus rogercresseyi [15]. Diseases caused by viruses are one of the great challenges of Chilean salmon farming industry; the first virus being identified in Chile was IPNV, which is highly persistent and causes severe mortality.…”
Section: Microbiological Threats Facing Chilean Aquaculturementioning
confidence: 99%